Estimation of DNA sequence divergence from comparison of restriction endonuclease digests. - Upholt, W B (1977)
An estimation of the DNA sequence divergence between defined DNA secquences of individuals or species may be made from comparison by gel electrophoresis of restriction endonuclease digests. This analysis is applicable to purified DNA sequence of moderate complexity (1-100 X 10(6) daltons) which have diverged by base substitution of 0.5 to 25% of nucleotides.